Ցիվիլիարխիայի ինդեքսի մշակման փորձ - Ալեքսանյան Աշոտ (YSU Journal of International Affairs, 2016)
The article analyzes the methodological basis of the index of civiliarchy and popular in sociopolitical studies major indexes of democracy. The article discusses the possibility of building a multilevel theoretical model of civiliarchy, which describes the qualitative aspects of political, social, economic and cultural processes. Main indicators of the model of democracy are political, economic, social and cultural rights and freedoms, the effective protection of which provides security, participation, representation, control, accountability, transparency, dialogue, partnership, and development. The index of civiliarchy determines the appropriate levels of civiliarchic institutions. Comparative analysis of data democracy indices demonstrates the potential of a new civiliarchic approach.